Linguagem neutra e letramento inclusivo-incisivo - Carreira, Rosângela A. R. (Descentrada. Revista interdisciplinaria de feminismos y género.)
The article presents reflections on neutral and non-binary language in Brazil. For the constitution of the corpus, a survey was carried out in the editorial market for simple investigation, analysis of its use in everyday gender and documentary analysis in a public university. It presents the need for linguistic-discursive education perspectives in favor of inclusive and incisive literacies. This research is based on Tosi (2020); Butler (2011); Maingueneau (2018) and Street (2010), Negroni and Hall (2022), Cano, Carreira & Silva (2022). Physical-structural and pedagogical strategies for the constitution of social spaces and discourses spaces are some proposals for the subjects to feel represented.